Droit à la ville et contestation de l’ordre moral urbain en Turquie - Benoit Montabone (EchoGéo)
This article seeks to understand the reasons of the violent demonstrations in Turkish cities in June 2013. It demonstrates that the defense of a public green space in the heart of Istanbul is not the main driver of the revolt, but moreover the latter is the response of the secular people to the evolution of the ways of producing the city and of controlling the public spaces by the islamist ruling party AKP. Contesting at the same time neoliberalism, conservatism and neo-ottomanism, the demonstrators strike against the new urban moral order of the AKP, claiming for freedom in public spaces and far beyond for an effective right to the city.